A THEORETICAL STUDY ON CHEMICAL BONDING AND INFRARED SPECTRA OF SinM (M = Sc, Y; n = 1-10) CLUSTERS - Tu, Phan Dang Cam; Cuong, Nguyen Quoc; Ngan, Vu Thi; Quang, Duong Tuan; Trung, Nguyen Tien (Vietnam Journal of Science and Technology, 2016)
In this paper, we applied the B3P86 method and DGDZVP basis set to investigate electronic properties and infrared (IR) spectra for SinM (M = Sc, Y; n = 1-10) clusters. The NBO analyses show that electron transfers from the dopant atoms to silicon frame of the SinM clusters. It is remarkable that the Si-M bond is mainly formed by the overlaps of the 3s-AOs and 3p-AOs of Si atoms, and 3d-AOs and 4s-AOs of Sc (or 4d-AOs and AO-5s of Y). The chemical bonds in the SiM and Si2M clusters are dominated by the covalent character including sigma and pi bonds. In addition, the analysis of the IR spectra suggests that the vibrational modes of SinM clusters are delocalized over the whole cluster. Moreover, the high-frequency and strong-intensity modes usually involve the vibrations of the dopant atoms. The results of this work provide fundamental information for experimental studies on transition-metal doped silicon clusters.